The NILAI NILAI PENDIDIKAN KARAKTER ANAK USIA DINI DALAM KITAB SLOKANTARA - Harianti, Dwi - (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2024)
This research aims to determine the character education values in Slokantara’s book. This research conduct with qualitative method. The data source was obtained through literature study. The Slokantara book was used as primary literature which is supported by other Hindu literary sources. The research results show that there are religious, honesty, hard work, communicative/friendly, love of peace, responsibility and social care in the Slokantara book. The character education values ​​in the Slokantara book can be used as a reference in the early childhood education process for the formation of strong children. The process of internalizing character education values ​​can be carried out using various methods, including storytelling, field trips, role playing and experiments. Every child is expected to receive the best education process from family, school and society in order to create a person with good character.